2013
DOI: 10.1089/adt.2013.509
|View full text |Cite
|
Sign up to set email alerts
|

Dual Luciferase Assay for Secreted Luciferases Based onGaussiaand NanoLuc

Abstract: Just recently, NanoLuc, a new engineered luciferase based on the small subunit of the luciferase from Oplophorus gracilirostris was introduced. Like the luciferase from Gaussia princeps, this luciferase is secreted into the medium. Both luciferases are the smallest and brightest luciferases known and well-suited for reporter assays. In our experiments, we demonstrate that both luciferases can be used together in a dual-reporter assay by solving the problem that NanoLuc produces a significant signal with coelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The coelenterazine analogue furimazine, in combination with NanoLuc, was found to produce the brightest output, and enhanced stability. Despite its relatively recent introduction, NanoLuc has already been used to generate a wide variety of transgenic organisms and cells for in vivo [ 71 78 ] and in vitro [ 79 96 ] studies, most of which have reported the considerable advantages of NanoLuc as a luminescent system, including the possibility of doing dual or multiplex assays in combination with Gaussia [ 82 ], or firefly [ 72 , 94 ] luciferases. Among the transgenic organisms using this technology, NanoLuc-expressing P. falciparum parasites (termed PfNLuc) have already been generated, and used for inhibitory compound screening assays, and protein secretion studies [ 97 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coelenterazine analogue furimazine, in combination with NanoLuc, was found to produce the brightest output, and enhanced stability. Despite its relatively recent introduction, NanoLuc has already been used to generate a wide variety of transgenic organisms and cells for in vivo [ 71 78 ] and in vitro [ 79 96 ] studies, most of which have reported the considerable advantages of NanoLuc as a luminescent system, including the possibility of doing dual or multiplex assays in combination with Gaussia [ 82 ], or firefly [ 72 , 94 ] luciferases. Among the transgenic organisms using this technology, NanoLuc-expressing P. falciparum parasites (termed PfNLuc) have already been generated, and used for inhibitory compound screening assays, and protein secretion studies [ 97 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another innovation incorporates the use of two luciferases with emissions that can be deduced from partially overlapping substrate usage, i.e., one substrate is used by both luciferases and a second substrate is used by only one 42 . More advanced innovations toward multiplexing allow for the simultaneous detection of three luciferases with activities that can be spectrally distinguished using appropriate emission filters after the addition of one 18 or more substrates 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Use of an NLuc inhibitor to separate enzymatic activities provides a simple approach to multiplexing the enzymes. Previous work described a dual luciferase assay to measure NLuc and GLuc activity based on mathematical extrapolation instead of direct measurement [19], however there were caveats to this approach. Using methyl 4-(4-ethoxy-3-methoxyphenyl)-2-methyl-5-oxo-1,4-dihydroindeno[1,2-b] pyridine-3-carboxylate [20], to inhibit ~99% of NLuc activity we were able to isolate GLuc activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, GLuc catalyzes the oxidation of coelenterazine (CTZ) to coelenteramide, also producing light in an ATP-independent reaction [18]. Assaying the enzymes in combination is limited primarily by two properties: 1) NLuc has substantial activity towards CTZ, an analog of FMZ [19]; and 2) the broad emission spectra are highly similar, with a maximum emission at 460 nm for NLuc and 480 nm for GLuc [16, 18]. Previous work focusing on a computational approach to discern luciferase activities from dual-transfected samples has been described, but is not amenable for longitudinal in vivo studies [19].…”
Section: Introductionmentioning
confidence: 99%